Peran Mediasi Kepuasan Pelanggan dalam Hubungan Bauran Pemasaran, Kualitas Layanan, dan Citra Merek terhadap Niat Pembelian Ulang - Erma Yusida (MAN 4 Kota Pekanbaru, 2025)
This study examines the influence of marketing mix, service quality, and brand image on repurchase intention, with customer satisfaction as a mediating variable, at Warung Bakso Presiden in Tulungagung. The research is driven by the intense competition among culinary MSMEs, necessitating strategic customer retention. Using a quantitative approach, data were gathered from 100 respondents via accidental sampling. Data analysis was conducted using path analysis. The results demonstrate that marketing mix, service quality, and brand image exert positive and significant effects on both customer satisfaction and repurchase intention. Furthermore, customer satisfaction partially mediates these relationships. The novelty of this study lies in its integrated analysis of three marketing constructs within the local culinary MSME sector. These findings offer practical implications for practitioners to optimize marketing strategies and service quality to foster customer loyalty and ensure long-term business sustainability.